Pharyngeal clearance and pharyngeal transit time determined by a biomagnetic method in normal humans - Miquelin, C. A.; Braga, FJHN; Dantas, R. O.; Oliveira, R. B.; Baffa, O. (Springer, 2001)
Clearance and transit time are parameters of great value in studies of digestive transit. Such parameters are nowadays obtained by means of scintigraphy and videofluoroscopy, with each technique having advantages and disadvantages. In this study we present a new, noninvasive method to study swallowing pharyngeal clearance (PC) and pharyngeal transit time (PTT). This new method is based on variations of magnetic flux produced by a magnetic bolus passing through the pharynx and detected by an AC biosusceptometer (ACB). These measurements may be performed in a simple way. cause no discomfort. and do not use radiation. We measured PC in 8 volunteers (7 males and I female. 23-33 years old) and PTT in 8 other volunteers (7 males and I female. 21-29 years old). PC was 0.82 +/- 0.10 s (mean +/- SD) and PTT was 0.75 +/- 0.03 s. The results were similar for PC but longer for PTT than those determined by means of other techniques. We conclude that the biomagnetic method can be used to evaluate PC and PTT.
Keywords: pharyngeal clearance; pharyngeal transit time; magnetism; biomagnetism; biosusceptometer; deglutition; deglutition disorders